Protein content and amino acid composition of eggs and endotrophic larvae from wild and captive fed sea urchin Paracentrotus lividus (Echinodermata: Echinoidea) - Gago, João (2020)
Knowledge on the biochemistry of proteins and amino acids (AA) of eggs and larvae of echinoids is scarce and the possibility to modify their profiles by diet manipulations is unknown. The protein content of eggs, prisms and pre‐plutei and the amino acid composition of eggs of Paracentrotus lividus from captive broodstock fed prepared diets were analysed and compared with the ones obtained from wild broodstock. Diets differed on protein source (fish or soy meals) and on protein content (10–40% dry weight – DW). Total and soluble protein content of both eggs and larvae was higher than 400 g kg−1 DW and 200 g kg−1 DW respectively. Glycine was the most abundant free AA. Very few differences were found among P. lividus eggs and larvae biochemical parameters, suggesting that their AA composition can hardly be changed by broodstock diet manipulations.